Resposta :
Resposta: Letra D (-2 e -3)
Explicação passo a passo:
[tex]x^{1}[/tex] + [tex]x^{2}[/tex] = -(b/a)
[tex]x^{1}[/tex] + [tex]x^{2}[/tex] = -(5/1)
[tex]x^{1}[/tex] + [tex]x^{2}[/tex] = -5
[tex]x^{1}[/tex] * [tex]x^{2}[/tex] = c/a
[tex]x^{1}[/tex] * [tex]x^{2}[/tex] = 6/1
[tex]x^{1}[/tex] * [tex]x^{2}[/tex] = 6
[tex]x^{1}[/tex] + [tex]x^{2}[/tex] = -5
[tex]x^{1}[/tex] * [tex]x^{2}[/tex] = 6
(-2) + (-3) = -5
(-2) * (-3) = 6
Foi mal, só quero pontos, dsclp :)
(só pq vc fez isso lá na outra pergunta).